Analisis Pengaruh NPF, FDR dan BOPO TERHADAP Profitabilitas (ROA) Pada PT Bank Muamalat Indonesia Tbk (Tahun 2011-2020) - Arsyi Sabana, Adzil; Wahid Mongkito, Abdul; Mariati, Siti (MADINAH, 2022)
This study aims to determine NPF, FDR and Bopo on Profitability (Roa) at Bank Muamalat Indonesia in 2011-2020. Data collection techniques in this study used literature study and decommentation methods. The data is processed using SPSS through the classical assumption test, path analysis test (Path) and hypothesis testing to see the effect of the independent variable X on the dependent variable through an intermediary variable and without going through an intermediary. From the results of data processing, it shows that the analysis of the effect of Npf, Fdr and Bopo on Profitability (Roa) at Pt Bank Muamalat Indonesia, Tbk. The results of the study show that: the effect of the NPF variable (X1) on BOPO (X3) is obtained by a value of 0.270 > 0.05 that there is no direct effect of X1 on X3. The effect of the variable FDR (X2) on BOPO (X3) obtained a value of 0.599 > 0.05 that there was no direct effect of FDR (X2) on BOPO (X3). The effect of the BOPO variable (X3) on ROA (Y) obtained a value of 0.000 ˂ 0.05 that there is a direct effect of BOPO (X3) on ROA (Y). The effect of the NPF variable (X1) on ROA (Y) through BOPO (X3) obtained a value of 0.011 > -0.450 that the direct effect is greater than the indirect effect which means NPF (X1) through BOPO (X3) has no significant effect on ROA (Y ). The effect of NPF (X1) on ROA (Y) through BOPO (X3) obtained a value of 0.207 > -0.047 that the indirect effect is greater than the direct effect which means FDR (X2) through BOPO (X3) has a significance for ROA (Y). The effect of NPF (X1) on ROA (Y) was obtained by a value of 0.819 > 0.05, indicating that there was no direct significant effect of NPF (X1) on ROA (Y). The effect of FDR (X2) on ROA (Y) was obtained by a value of 0.322 > 0.05, indicating that there was no direct significant effect of FDR (X2) on ROA (Y).